GAMBARAN FOLLOWERSHIP PADA KARYAWAN SHM - Mirna Efar; Hana Panggabean (MANASA, 2015)
The aim of this study is to describe the followership type of the employees of SHM—an organization committed in printed media. By knowing the followership type of its employees, an organization can manage each of them efficiently to achieve the organization’s goal. Because a leader’s contribution is less than the workers’ contribution for the organizational success, knowing the employees’ followership type is pivotal for the further management of each worker. This study used quantitative approach, using followership questionnaire developed by Robert Kelley. The questionnaires were distributed to all SHM employees, with the total of 99 workers. The results showed that SHM employees are mostly pragmatic followers (53.12%), while the rest are exemplary followers (46.88%). The intervention recommendation was informed to the higher-ups using survey-feedback framework; the information included the followership type of SHM employees and the effective way to manage them.